An Updated Meta-Analysis of the Relationship Between Helicobacter pylori Infection and the Risk of Coronary Heart Disease - Tong, Ling; Wang, Bei-Bei; Li, Fei-Hong; Lv, Shu-Ping; Pan, Fei-Fei; Dong, Xin-Jiang (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: coronary heart disease (CHD) is one of the leading causes of mortality in the world. Although the traditional risk factors for CHD have been identified, it seems that there are still many CHD without these factors. Previous studies have hypothesized that Helicobacter pylori (H. pylori ) infection was associated with risk of CHD. Objective: The association between H. pylori infection and risk of CHD was studied by a using systematic evaluation and meta-analysis method. Methods: In order to find relevant studies, four electronic databases were searched system- atically until August 2021. According to the inclusion and exclusion criteria, studies were screened and data was extracted. Under the random-effect or fixed-random model, the odds ratio (OR) and 95% confidence interval (95% CI) were combined. All analyses were conducted by using review manager 5.4. Results: Among the included studies, 2 studies were analyzed for H. pylori stool antigen test, 2 studies were analyzed for H. pylori histological staining test, 13 studies were analyzed for anti-CagA test, and 38 studies were analyzed for anti-H. pylori IgG test. The pooled results revealed that positive anti-H. pylori IgG was significantly associated with increased risk of CHD (OR, 1.58; 95% CI:1.34-1.87). Similarly, positive anti-Cag A, positive H. pylori stool antigen, and positive H. pylori histological staining were significantly associated with development of CHD with (OR:1.33,95%CI:1.16-1.53), (OR:3.50,95%CI:1.60-7.66) and (OR:1.78,95% CI:1.12-2.83), respectively. Conclusions: This meta-analysis showed that H. pylori infection increased risk of CHD. However, more studies are needed to further investigate whether early eradication of H. pylori may reduce the morbidity of CHD.